Strategi Pemulihan Citra STAIN Curup - Sumarni Sumai; Adinda Tessa Naumi (Jurnal Dakwah dan Komunikasi, 2016)
The wide-spread news which tarnished the name of STAIN Curup cause a negative image of this institution in community. It can be seen from the decreasing of public interest to learn at STAIN Curup by the decline in number of participants followed selections in STAIN Curup at 2013-2015. This study aims to provide an overview and in-depth explanation about the image restoration strategies of STAIN Curup. This research was conducted using qualitative method with a case study approach. The data collecting done by observations, interviews, documentary studies, and data analysis to find answers to; (1) How is the strategy of STAIN Curup to recover its image? (2) What are the obstacles in recovering the image of STAIN Curup? The results showed that the strategy done by STAIN Curup is promotion to the schools annually. The inhibiting factors are: first, tactic. The tactic used in image restoration of STAIN Curup concentrated just on one form, namely the school to school promotion. The second factor is the role and tasks of Public Relation. The roles and tasks are not maximized, PR is just still reputed as the sender of letters. The third factor is the organizational communication. It is not running properly. Communication within an organization plays an important role, without it the organizational life will be fragile, can not grow and even die maybe.